PENGARUH MOTIVASI DAN DISIPLIN TERHADAP KINERJA KARYAWAN PT PUPUK ISKANDAR MUDA (Negotium: Jurnal Ilmu Administrasi Bisnis, 2022)
This study aims to examine the effect of motivation and discipline on the performance of employees of PT Pupuk Iskandar Muda. This research was conducted at PT Pupuk Iskandar Muda. The population in this study were employees of PT Pupuk Iskandar Muda totaling 558 people, and the determination of the sample using the "probability random sampling" technique and the formula used in determining the number of respondents using the slovin formula so that the number of respondents was 85 people. The data analysis technique used is descriptive analysis and multiple linear regression analysis, instrument test and classical assumption test using SPSS version 25 software. Partial test results show that the motivation variable has a positive and significant effect on performance, while discipline has a positive and significant effect on performance. performance. Simultaneously shows that motivation and discipline have a significant effect on performance. Discipline variable is the most dominant variable influencing performance. Keyword: Motivation, Discipline and Employee Performance.